PENGUJIAN PENYAKIT KOMODITAS IKAN AIR TAWAR PADA LALU LINTAS DOMESTIK DI STASIUN KARANTINA IKAN JAMBI - Hamdani Hamdani; Apricilia Caroline; Sarifah Aini; Angkasa Putra; Herianto Suriadin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Increased trade flows of international and domestic fishery coomodities in the opportunity to enter and spread Hama penyakit Ikan Karantina (HPIK) caused by pathogenic organism, namely bacteria, parasites, fungi, and viruses. This study aims to identify whether freshwater fish commodities in domestic traffic are infected with parasites, the bacteria Edwardsiella ictaluri, TiLV (Tilapia lake Virus) and the fungus Aphanomyces invadans at the Fish Quarantine Stasion, Quality Control and Safety of Fishery Products Jambi. Fish samples consist of 15 fish samples to be tranported. Based on results of the examinatoin of fish diseases, Parasite Examination there were 4 parasites with 3 types of parasites, namely 2 parasites of Dactylogyrus sp. On the gills of Tilapia and catfish. One (1) parasite Gyrodactylus sp. On fish slime Stripe 3, and 1 parasite Camallanus sp.in the intestines of betta fish; on bacterial examination of the 4 samples of fish examined, Edwardsiella ictaluri bacteria were nof found; on virus examination the result were negative for TiLV (Tilapia lake Virus); on examination of the fungus with the PCR method, negatif result were obtained for the fungus Aphanomyces invadans which is the cause of EUS (Epizootic Ulcerative Syndrome).